Restorative Justice: A Model of Fair Traffic Accident Resolution - Sutrasno, S. Andi; Prastyanti, Rina Arum (International Journal of Global Community, 2021)
The principle of traffic accident case resolution in Indonesia has been governed in Article 310 of Law No.22 of 2009 about UULAJ (Traffic and Road Transportation Act) and Law No.8 of 1981 about KUHAP (Code of Criminal Procedure) does not know the resolution with penal mediation. Considering the data of research, it can be seen that the penal mediation rate for Sragen and Boyolali Resort Polices (Polres Sragen and Polres Boyolali) is 95%, while that for Polres Ciamis is 49.3%. The resolution does not realize the justice because there is no justice and law certainty, as it results in three resolution motifs: pure penal mediation, impure penal mediation, and penal. The recommendation given to the ideal resolution of traffic accident case is to revise the Article 310 of UULAJ by adding two clauses to give the victim and the perpetrator the opportunity of reconciling as restitutive attempt to realize justice, certainty, and usefulness. The process of restoration is conducted through penal mediation, Victim offender Mediation(VOM), giving the mediator a space to help the resolution of conflict between victim and perpetrator. This model can be applied at investigation level, prosecution, or trial level.